Kinematics of the intermediate-mass black hole candidate HLX-1 - Soria, Roberto; Hau, G.; Pakull, M. (Institute of Physics Publishing, 2013)
We studied the optical spectrum of HLX-1 during its latest outburst, using the FORS2 spectrograph on the Very Large Telescope. We detect an Hα emission line centered at λ = 6718.9 ± 0.9 Å and find that its projected radial velocity with respect to the nucleus of ESO 243–49 is 424 ± 27 km s–1, while the maximum rotational velocity of the stars in that galaxy is 209 km s–1. This suggests that HLX-1 and its surrounding stars were not formed in situ, but came either from a disrupted dwarf galaxy or from a nuclear recoil. We also find that the Hα emission line is resolved with FWHM 400 km s–1, suggesting a nebular rather than disk origin for the emission. Its luminosity (L Hα = a few 1037 erg s–1, equivalent width = 70 Å) is also consistent with emission from a nebula photoionized by HLX-1.